2008
DOI: 10.1080/10705420802255122
|View full text |Cite
|
Sign up to set email alerts
|

Interdisciplinary Community Collaboration: Perspectives of Community Practitioners on Successful Strategies

Abstract: Six focus groups were convened to collect data on successful interdisciplinary community collaboration (ICC) strategies. Participants came from a variety of disciplines but shared the common identification of having worked in similar communities. Participant assignment to one of six groups was designed to insure diversity by gender and race or ethnicity. They discussed four questions received in advance. Prior consented taperecorded sessions were transcribed and reviewed by group facilitators using a process o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 22 publications
1
15
0
Order By: Relevance
“…Examples are a lack of legitimacy among colleagues and a need to reduce costs. The cases confirm earlier research that boundary spanners need to possess a variety of competencies and be able to perform a variety of strategies (e.g., Bayne-Smith, Mizrahi, & Garcia, 2008).…”
Section: Discussionsupporting
confidence: 86%
“…Examples are a lack of legitimacy among colleagues and a need to reduce costs. The cases confirm earlier research that boundary spanners need to possess a variety of competencies and be able to perform a variety of strategies (e.g., Bayne-Smith, Mizrahi, & Garcia, 2008).…”
Section: Discussionsupporting
confidence: 86%
“…The findings from this study affirm the importance of many elements of successful collaboration that are reflected in social work literature: strong leadership; shared vision; structures and processes to facilitate the creation and evolution of collaborative efforts; role clarity; defined goals; attention to member composition, relationship building, and team building; and achievement of interim successes (Bertram, 2008;Dunlop & Holosko, 2004;Ferguson, 2004;Fitch, 2009;Harbert, 1997;Jones, Crook, & Webb, 2007;Reilly, 2001;Slaght & Hamilton, 2005;Spath, Werrbach, & Pine, 2008;Urwin, 1998). The importance of trust, communication, shared vision, and adoption of values consistent with collaboration among stakeholders and facilitators is also reflected in the literature (Bayne- Smith, Mizrahi, & Garcia, 2008;Jones et al, 2007;Potito, Day, Carson, & O'Leary, 2009). Findings from this study are also consistent with other studies that found multiple factors that impede collaboration, such as conflicts in perspectives and priorities, staff turnover, barriers to sharing confidential information, and changes in systems and resources (Altshuler, 2003;Darlington, Feeney, & Rixon, 2005;Han, Carnochan, & Austin, 2007;Ryan, Tracy, Rebeck, Biegel, & Johnsen, 2001;Spath et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Coalition building commonly involves organizations from different disciplines (Korazim-Kõrösy et al, 2007) and/or multiple sectors (Selsky & Parker, 2005). The term coalition is often used interchangeably in practice and research with other terms, such as collaboration, collaborative (Bayne-Smith, Mizrahi, and Garcia, 2008), or interorganizational partnerships (Alter, 2009). Hill and Lynn (2003) posited that nonprofit organizations will partner with other organizations to produce goods and services, and Sowa (2009) asserted that they also collaborate to increase overall organizational capacity.…”
Section: Background Nonprofit Organizations and Lobbyingmentioning
confidence: 99%